JANTURAN JEJER PERTAMA DALAM PERGELARAN WAYANG KULIT: ANALISIS GEOCRITICISM BERTRAND WESTPHAL - Rokhim, Mukhammad Nur; Nugroho, Yusro Edy (Pusat Riset Manuskrip, Literatur, dan Tradisi Lisan, 2023)
In the first row of shadow puppet performances, distinctive differences exist in presenting regional differentiation between India and Java. Therefore, a geocentric study is necessary to analyse geosphere differences in wayang kulit sequences. This research aims to describe geographical and geophilosophical concepts in the narrative of the first line of a shadow puppet performance. This study uses a qualitative approach, while the data is reviewed from the perspective of geocriticism theory. Survey of data using a note-taking model from recordings of shadow puppet performances, as well as analysis of text interpretations that focus on the first line of the principal kingdoms, namely Amarta-Astina (Mahabharata) and Pancawati-Alengka (Ramayana). From this analysis, it can be concluded that the narrative of the first line of a wayang kulit performance, such as the expression flanked by the ocean (ginapit ing samodra), having a large harbour (ngayunaken Bandaran Ageng), and pasir wukir (coast and mountains) describes the geography of Java. The spatiotemporal aspects in first ‘jejer’ of the Mahabharata and Ramayana have similarities, namely, the life of urban society in the royal capital and rural communities. The element of transgressiveness is manifested in the geophilosophical application of empire for prosperity. Referentiality is influenced by the essential dissimilarity of wayang stories, which are more Javanese-centric.